Combined Effects of Load Factors and Booking Time on Fares: Insights from the Yield Management of a Low-Cost Airline - Marco Alderighi; Marcella Nicolini; Claudio A. Piga (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
Based on two strands of theoretical research, this paper provides new evidence on how fares are jointly affected by in-flight seat availability and purchasing date. As capacity-driven theories predict, it emerges that fares monotonically and substantially increase with the flights occupancy rate. Moreover, as suggested in the literature on intertemporal price discrimination, the adoption of advance purchase discounts is widespread as the departure date nears, but it may be part of a U-shaped temporal profile, where discounts are preceded by periods of relatively higher fares. Finally, the intervention of yield management analysts appears to play a substantial role.
Keywords: D22; L11; L93; 330; Pricing policy; Panel Data; Ryanair; Yield Management